Penurunan Intensitas Nyeri Pada Pasien Fraktur Tertutup Dengan Pemberian Terapi Kompres Dingin Di Ruangan IGD RSUD Prof. Dr. H. ALOEI SABOE - Jerliawanti Tuna; Pipin Yunus (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
The research aims to determine the reduction in pain intensity in closed fracture patients by administering cold compress therapy in the emergency room at RSAS Prof. Dr. H. Aloe Saboe Gorontalo City. Students are able to apply cold compress therapy to reduce the intensity of pain in closed fracture patients. Knowing the intensity of pain in closed fracture patients before giving cold compress therapy. Knowing the intensity of pain in closed fracture patients after giving cold compress therapy. This research method is quantitative research using a quasi-experimental design that provides treatment or intervention to research subjects and then the effects of the treatment are measured and analyzed. The research design used was a pre post test group design approach. This design was used to compare pain levels before and after applying cold compresses to closed fracture patients. The results of the research that has been carried out show: The subject's pain scale before applying the cold compress was included in the moderate pain scale where in subject I the pain scale was 7 and respondent II's pain scale was 9. After applying the cold compress, there was a decrease in the pain scale in both respondents to a moderate level. where in subject I the pain scale was 5 and in subject II the pain scale was 6. Giving cold compress therapy could reduce the intensity of pain in closed fracture patients in the emergency room at RSAS Prof. Dr. H. Aloe Saboe Gorontalo City.